Restoration - Hoffman, Michael; Walters, Rupert; Downey, Robert, 1965-; Neill, Sam; Ryan, Meg; Howard, James Newton; Tremain, Rose; Miramax Films; Segue Productions; Avenue Pictures; Oxford Film Company; Miramax Home Entertainment (Firm); et al. (Burbank, CA : Miramax Home Entertainment, 2003)
Merivel abandons his medical studies to revel in gluttony, indolence, & buffoonery at the court of King Charles II. When he falls in love with the royal mistress he is banished from court, leading to work in a Quaker Bedlam.
Based on the novel by Rose Tremain.
Originally released as a motion picture in 1995.
Features: production feaurette, theatrical trailer, chapter search.
Director of photography, Oliver Stapleton; production design, Eugenio Zanetti; editor, Garth Craven; music, James Newton Howard.
Robert Downey, Jr., Sam Neill, Meg Ryan, David Thewlis, Polly Walker, Ian McKellen, Hugh Grant.
MPAA rating: R.
Keywords: Tremain, Rose -- Film and video adaptations; Video recordings for hard of hearing people; Great Britain -- History -- Charles II, 1660-1685 -- Drama; Based on the book; Feature films